Incorporation of thermal explosion scenarios into the multilevel risk analysis procedure - Mašín, Jindřich; Ferjenčík, Miloš (John Wiley & Sons Ltd., 2021)
The work's starting point is the multilevel risk analysis procedure (MLRAP), the difficulty of which sits comfortably between the easiest qualitative risk studies and the most complicated quantitative analysis. MLRAP was originally developed for use in explosive-handling plants. During the application of MLRAP, a gap in the procedure was found. The approach was not easily applicable to functional nodes with possible exothermic reactions. This article aims to the identification of a reasonable number of layer of protection analysis thermal explosion scenarios for such functional nodes. Two tools are utilized for this purpose: the Stoessel's concept of criticality classes and the use of adiabatic calorimetry results to classify functional nodes with the possibility of an exothermic reaction. The article modifies the original MLRAP so that for functional nodes where an exothermic reaction is possible, it identifies initiating events and scenarios depending on the criticality class and the type of reactor. A detailed flow chart complements the modification of MLRAP. The application of the modified MLRAP for the identification of thermal runaway scenarios not only in the explosive-handling processes is illustrated by two examples.
Začlenění scénářů tepelného výbuchu do víceúrovňového postupu analýzy rizika
Keywords: hazards evaluation; risk assessment; oceňování zdrojů rizika; hodnocení rizika